2022
DOI: 10.2169/internalmedicine.8413-21
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and Meningoencephalitis Due to Varicella-zoster Virus Reinfection and Epstein-Barr Virus Reactivation in a Patient with Rheumatoid Arthritis

Abstract: A 72-year-old woman with rheumatoid arthritis was treated with methotrexate (MTX) and iguratimod. Upon examination of a liver tumor, blisters due to varicella-zoster virus (VZV) infection were observed. Despite oral administration of valacyclovir, she developed varicella pneumonia and meningoencephalitis. A VZV antibody test revealed reinfection. The liver tumor shrank after discontinuance of MTX, and polymerase chain reaction revealed the reactivation of the Epstein-Barr virus (EBV). Therefore, we were unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Previous studies reported that other CNS infections could trigger EBV reactivation in immunocompromised patients (9). Two case reports described VZV infections associated with EBV reactivation (10,11). However, some reports have discussed the need for careful clinical determination of whether EBV is the true cause of or merely a bystander in CNS infections, as EBV can occasionally be detected along with other CNS infections in immunocompromised patients (9,12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that other CNS infections could trigger EBV reactivation in immunocompromised patients (9). Two case reports described VZV infections associated with EBV reactivation (10,11). However, some reports have discussed the need for careful clinical determination of whether EBV is the true cause of or merely a bystander in CNS infections, as EBV can occasionally be detected along with other CNS infections in immunocompromised patients (9,12).…”
Section: Discussionmentioning
confidence: 99%
“…Although primary varicella-zoster virus (VZV) infection in children is generally mild, VZV infection or reactivation in adults or immunocompromised patients can lead to a severe presentation [1] . Several studies have reported VZV pneumonia in immunocompromised patients [2] , [3] , [4] . However, to the best of our knowledge, none of the reports have described the clinical course of VZV pneumonia focusing on the time course of skin rash, chest computed tomography (CT) findings, viral load, and antibody titer.…”
Section: Introductionmentioning
confidence: 99%